MEDIA-REALITY IN THE VISUAL ARTS / МЕДИАРЕАЛЬНОСТЬ В ИЗОБРАЗИТЕЛЬНОМ ИСКУССТВЕ - YUGAY INGA I. / ЮГАЙ И.И. (Наука телевидения, 2019)
The article researches the influence of the media on contemporary visual arts in its aesthetic, technological and sociocultural aspects. The author stems from the fact that in the works of contemporary artists the influence of media reality becomes more and more discernible on the level of theme, means of presentation and application of expressive means. The article analyzes paintings by contemporary painters pertaining to different countries and generations. In the series of portraits by Finnish painter Sami Lukkarinen interpretation is given to the manifestation of the human being in social media, while digital depiction is posed as a symbol of the search for identity and self-expression in the media environment. In the works of American-British artist Cathy Backett, American artist Jennifer Krauze Chappeau and Finnish artist Paula Olikainen analysis is made of the application of technical-technological and aesthetic solutions characteristic for media: photography, cinema, television and digital depiction. As an example of reflection in the visual arts of the new procedurality characteristic for media, examination is made of German artist Urs Fischer. In the author’s opinion, the features of the new procedurality are repeat accuracy, algorithm development and subservience to the digital, programming and hardware-based range of tools. In Fischer’s works the new procedurality is manifested in the sequence built according to the principle of the fixation of the stages of transformation of the picture, as well as the approaches towards form and color characteristic to animation of morphing. Special attention is paid to the works of artist from New Zealand Jeremy Geddes, who demonstrates in his works the attempts of new forms of mass culture: computer and video games. Being a form of virtual reality, computer games makes it possible to repudiate physical laws and embody any type of logic and rules into the created world. The ideas expounded by the author make it possible to interpret contemporary works of art, taking into account the transformations which took place as the result of the transferal of the reality of human activities into meta-reality.